The financial crisis and citizens' trust in the European Central Bank - Felix Roth; Daniel Gros (Verein für Socialpolitik, 2010)
Trust in the ECB, as measured by the standard Eurobarometer surveys has fallen to unprecedented lows - especially in the larger euro area countries. We find that up to the start of the recession in 2008 trust in the ECB was little affected by business cycle variables such as growth and even inflation. This changed radically with the recession, with trust in the ECB being correlated quite closely with growth. However, even the recovery of growth in 2009 was not sufficient to restore trust in the ECB to previous levels. This finding implies that European citizens seem to have heavily blamed the European Central Bank for the real economic downturn caused by the financial crisis.
Keywords: E58; G21; Z13; 330; Financial Crisis; Trust; European Central Bank